Anticoagulant and anti-platelet effects are maintained following coadministration of otamixaban, a direct factor Xa inhibitor, and acetylsalicylic acid - Hinder, Markus; Frick, Annke; Rosenburg, Ronald; Hesse, Galina; Ozoux, Marie-Laure; Laux, Volker; Scholtz, Herman; Gebauer, Alexander; Paccaly, Anne (Thrombosis and Haemostasis, 2006)
The pharmacokinetics, pharmacodynamics and safety of the direct factor Xa inhibitor, otamixaban, with and without concomitant acetylsalicylic acid (ASA) were investigated in healthy volunteers. The study was a double-blind, placebo-controlled 3-way crossover study. Sixty-eight male volunteers in total were randomised to otamixaban, ASA, or otamixaban with ASA. ASA (300 mg once a day) was started2 days before and continued on the day of the otamixaban 6-hour IV infusion (0.3 and 0.5 mg/kg). Pharmacokinetic and pharmacodynamic parameters (coagulation markers, platelet function tests and skin bleeding time) were determined. Drug interaction was assessed by the ratios of geometric means and 90 confidence intervals (90% CI)of the parameter estimates.Pharmacokinetic parameters of otamixaban remain ed unchanged with ASA. Ratios of geometric means (90% CI) were for Ceoi 96.54 (91.21–102.19) and 95. 04 (90. 10–100. 24) and for AUC 98. 0 (93. 92–102. 25) and 95. 90 (92. 61–99. 31), for 0. 3 and 0. 5 mg/kg, respectively. No drug interaction was observed between otamixaban andASA on the coagulation and platelet function parameters. Neither otamixaban nor ASA had an effect on skin bleeding time; their co-administration led toa slight prolongation of skin bleeding time above the normal range without any clinically relevant bleeding. This study demonstrated that the desired effects of otamixaban and ASA, namely anticoagulation and platelet inhibition, respectively, are maintained during co-administration of both drugs.
Keywords: Acetylsalicylic acid; coagulation; factor Xa; pharmacokinetics; pharmacodynamics; otamixaban